advertisement

Do Now Solve using elimination: 3x + 2y = – 19 – 3x – 5y = 25 Homework Solutions 1) x – y = 1 + x + y = 3 2x = 4 x = 2 2+ y = 3 y = 1 Solution: (2, 1) Homework Solutions 3) x + 4y – x – 6y 10y y = 11 = 11 = 0 = 0 x + 4(0) = 11 x = 11 Solution: (11, 0) Homework Solutions 5) 3x + 4y = 19 – 3x + 6y = 33 -2y = -14 y = 7 3x + 4(7) = 19 3x + 28 = 19 3x = -9 x = -3 Solution: (-3, 7) Homework Solutions 7) 3a + 4b = 2 + 4a – 4b = 12 7a = 14 a = 2 3(2) + 4b = 2 6 + 4b = 2 4b = -4 b = -1 Solution: (2, -1) Homework Solutions 9) 2x – 3y = 9 – -5x – 3y = 30 7x = -21 x = -3 2(-3) – 3y = 9 -6 – 3y = 9 -3y = 15 y = -5 Solution: (-3, -5) 6s + 2t = 24 4s + 2t = 18 The coefficients of one of the variables are not always going to be the same. When neither variable’s coefficients are the same, you can’t eliminate one variable just by adding or subtracting. Sometimes we have to MULTIPLY one or both equations to make the coefficients of one of the variables the same. 3x + 4y = 6 5x + 2y = – 4 3x + 2y = 0 x – 5y = 17 4c – 3d = 22 2c – d = 10 8 x 3 y 11 2 x 5 y 27 4x 5 y 6 6 x 7 y 20 5 x 3 y 12 4 x 5 y 17 3x + 2y = – 9 5x – 3y = 4 Homework Worksheet pg. 423 #’s 1, 4, 7, 10